2021
DOI: 10.1021/jacs.1c01466
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective CO2 Electroreduction to C2H4 Using a Metal–Organic Framework with Dual Active Sites

Abstract: Conversion from CO 2 to C 2 H 4 is important for the development of energy and the environment, but the high energy barrier of hydrogenation of the *CO intermediate and C−C coupling step tend to result in C 1 compounds as the main product and thus restrict the generation of C 2 H 4 . Here, we report a metal−organic framework (denoted as PcCu-Cu-O), composed of 2,3,9,10,16,17,23,24-octahydroxyphthalo-cyaninato)copper(II) (PcCu-(OH) 8 ) ligands and the square-planar CuO 4 nodes, as the electrocatalyst for CO 2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
218
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(225 citation statements)
references
References 39 publications
7
218
0
Order By: Relevance
“…Main eCO 2 RR products were identified as CO at low current density and C 2 H 4 at high current density. For the NH 2 -Cu-BDC and OH-Cu-BDC [2,12,[27][28][29][30][31][32][33] (Table S1, Supporting Information). Black square for the results in the literature.…”
Section: Eco2rr Performance Evaluation Of X-cu-bdcmentioning
confidence: 99%
See 1 more Smart Citation
“…Main eCO 2 RR products were identified as CO at low current density and C 2 H 4 at high current density. For the NH 2 -Cu-BDC and OH-Cu-BDC [2,12,[27][28][29][30][31][32][33] (Table S1, Supporting Information). Black square for the results in the literature.…”
Section: Eco2rr Performance Evaluation Of X-cu-bdcmentioning
confidence: 99%
“…2F-Cu-BDC ranks high in the comparison with the prior best results in literature. [2,12,[27][28][29][30][31][32][33] It also should be noted that although a few catalysts exhibit high R C2/C1 (such as ref. [ 33 ]), their current densities are impractical (<15 mA cm -2 ).…”
Section: Eco2rr Performance Evaluation Of X-cu-bdcmentioning
confidence: 99%
“…However, active‐site engineering in multimetal‐site MOFs may be a promising strategy for C−C dimerization from the perspective of chemistry. For example, Liao's group 69 found that the suitable distance between C 2 H 4 ‐producing and CO‐producing sites of MOF was easy for C 2 H 4 generation. In this study, they prepared PcCu‐Cu‐O MOF composed of PcCu‐(OH) 8 ligands and the square‐planar CuO 4 nodes for CO 2 RR.…”
Section: D Mofs For Co2rrmentioning
confidence: 99%
“…However, active-site engineering in multimetal-site MOFs may be a promising strategy for C−C dimerization from the perspective of chemistry. For example, Liao's group 69 found that the suitable distance between…”
Section: D Phthalocyanine-based Mofs For Co 2 Rrmentioning
confidence: 99%
“…[ 10 ] In spite of the enhanced CH 4 selectivity, almost all of the reported catalytic activities (assessed by j CH4 ) are <400 mA cm −2 to date, [ 9 ] which can be attributed to the low densities (typically < 10 wt%) of single‐atomic Cu catalytic sites inside the catalysts. Due to the limitation of maintaining the chemical environment of SAC sites, further increase of the Cu loading often results in close proximity of multiple‐atomic sites [ 13,14 ] and even aggregation, [ 15,16 ] and thus shifts the CO 2 RR pathway from CH 4 to C 2+ products due to the enhanced C–C coupling. For instance, it has been reported that when two Cu SAC sites get close enough, the coupling of two *CO intermediates is facilitated to form a *OC–CO dimer, leading to the increase of the C 2 H 4 /CH 4 ratio.…”
Section: Introductionmentioning
confidence: 99%